Progressive preoperative pneumoperitoneum and components separation in incisional hernia with loss of domain. A case study report - Guevara-Espejo, Jonah Salomon (2022)
Background: A hernia with loss of domain has a hernia sac content of 50% or more than the content of the abdominal cavity, which leads to local and systemic effects. Report case: The case of a patient with an incisional hernia with loss of domain and 30 years of evolution is presented, she underwent preoperative pneumoperitoneum and during surgery, anterior component separation was performed to avoid tension in the closure of the hernia defect. Conclusion: Preoperative progressive neumoperitoneum is a recommended method in the management of patients with giant hernias and loss of domain, because it is low cost, safe and easy to perform and avoids the possible complications that the closure of the defect with tension entails.